Perancangan Aplikasi Pengajuan Magang di Fakultas Syariah dan Hukum UINSU Berbasis Web - Ahmad Fariz Fuady; Dwiky Oldi Amsyah; Suhardi Suhardi (Lembaga Pengembangan Kinerja Dosen, 2025)
The internship application process at the Faculty of Sharia and Law, UIN Sumatera Utara, is still conducted manually, leading to various issues such as delayed information, unstructured administration, and inefficient communication between students, faculty, and partner institutions. To address these problems, a web-based internship application system was developed to help students access internship information, apply online, and assist faculty in verifying and monitoring the process. The development of this application uses the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. During the design phase, Unified Modeling Language (UML) was used, including use case diagrams, activity diagrams, and class diagrams to visualize the system’s structure and workflow. This application offers key features such as a list of partner institutions, internship vacancies, document submission, and application status notifications. The implementation of this web-based system is expected to make the internship application process faster, more transparent, well-organized, and supportive of the academic digitalization efforts at the Faculty of Sharia and Law, UIN Sumatera Utara.